The deterioration of residential neighborhoods and the challenges of developing them in Algerian cities. A case study of a neighborhood of 600 dwellings in the city of M’sila - Allal, Ahmed; Dehimi, Salim; Bediar, Adel; Benaissa, Fateh Toufik (Technium Social Sciences Journal, 2023)
Urban planning demands that the needs and problems resulting from the dynamics of society and its development should be taken into account, relying on the studies that consider the reality of the city and the factors influencing its daily life, so it can perform its function under favorable circumstances for a better future within the context of durable development. It should be remembered that the first imbalances of the urban space are those that followed the industrial revolution and the doctrines and intellectual trends. However, the modern trend in architecture and urbanization in terms of urban space is the most influential. Urban space becomes a scene of symbolic confrontations between the designer (imposed plans) and the users of space. This situation appears clearly in the deterioration of the urban space giving a significant transfer of a denial, because of its incompatibility with the needs of the population. The Algerian city has experienced, particularly after the independence, the same situation despite the diversity of cultural and cultural heritage because of several factors, including rapid urban growth. These factors marked the course of the reconstruction and thus the urban structure of the Algerian cities, which urged the search for solutions, hastily put in place, to this evolution which led to changes in the society, testifying a blatant failure to reach the ambitions of users when they were excluded during all stages of the urban project. This is why urban space is considered as consumer goods within the user's reach, although it should be considered as a process rather than a product. Our research work is axed on the inadequacy of the productive environment (living environment or urban space) in the city of M'sila and on the way of life of the population that uses this space for its needs and aspirations, which are expressed through unjustified user interventions in the perspective of adapting space to their way of life. The point is to focus on the user and his participation in the creation of a durable and suitable urban environment.